2020
DOI: 10.1523/jneurosci.0716-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptors/Epac Signaling Increases the Size of the Readily Releasable Pool of Synaptic Vesicles Required for Parallel Fiber LTP

Abstract: The second messenger cAMP is an important determinant of synaptic plasticity that is associated with enhanced neurotransmitter release. Long-term potentiation (LTP) at parallel fiber (PF)-Purkinje cell (PC) synapses depends on a Ca 21 -induced increase in presynaptic cAMP that is mediated by Ca 21 -sensitive adenylyl cyclases. However, the upstream signaling and the downstream targets of cAMP involved in these events remain poorly understood. It is unclear whether cAMP generated by b-adrenergic receptors (bARs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 83 publications
5
36
2
Order By: Relevance
“…Multiple intracellular molecules are involved in the process, such as protein phosphatases (PP1, PP2A, and PP2B), T-type Ca 2+ channels, and nitric oxide (Gutierrez-Castellanos, et al, 2017;Belmeguenai and Hansel, 2005;Kakegawa and Yuzaki, 2005;Lev-Ram, et al, 2002). Recent studies show that cAMP signaling activates the GluA2/GluA3-dependent AMPARs by enhancing their conductance, which induces LTP (Martin, et al, 2020;Gutierrez-Castellanos, et al, 2017). In our study, the cAMP agonist forskolin was equally efficient in inducing LTP in control and Celsr3 cKO slices.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Multiple intracellular molecules are involved in the process, such as protein phosphatases (PP1, PP2A, and PP2B), T-type Ca 2+ channels, and nitric oxide (Gutierrez-Castellanos, et al, 2017;Belmeguenai and Hansel, 2005;Kakegawa and Yuzaki, 2005;Lev-Ram, et al, 2002). Recent studies show that cAMP signaling activates the GluA2/GluA3-dependent AMPARs by enhancing their conductance, which induces LTP (Martin, et al, 2020;Gutierrez-Castellanos, et al, 2017). In our study, the cAMP agonist forskolin was equally efficient in inducing LTP in control and Celsr3 cKO slices.…”
Section: Discussionsupporting
confidence: 53%
“…The second messenger cyclic adenosine monophosphate (cAMP) is a key modulator of the PF-PC postsynaptic LTP, which is triggered by G-protein-coupled postsynaptic receptors such as adrenergic receptors (Martin, et al, 2020). To test whether cAMP activation induces LTP in PCs, the cAMP agonist forskolin was perfused in cerebellar slices during baseline recording of PCs.…”
Section: Facilitation Of Ltp Induction By Celsr3 Requires Wnt5a/camp Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit direct anatomical evidence of β-ARs in presynaptic terminals of glutamatergic CA1-subiculum synapses is still missing, transport of β-ARs from the soma of CA1 pyramidal cells (Hillman et al, 2005;Guo and Li, 2007) to presynaptic sites is possible. Interestingly, β-AR signaling via direct activation of the guanine nucleotide exchange protein Epac by cAMP is involved in LTP at cerebellar granule cell to Purkinje cell synapses (Martín et al, 2020). There, an increase in the number of synaptic vesicles primed for exocytosis accounts for the potentiation of neurotransmitter release driven by β-ARs.…”
Section: Discussionmentioning
confidence: 99%
“…Epac2 activity can strongly increase synaptic transmission (Fernandes et al, 2015;Gekel and Neher, 2008), yet a role in synapse formation has not been reported. Interestingly, Epac2 was recently found to be downstream of Gs-coupled β adrenergic receptors to mediate presynaptic LTP at parallel fiber synapses to Purkinje cells (Martín et al, 2020). cAMP signaling via PKA, Epac2 or Rho GTPases may affect the axonal cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%